(3GdGcJaG TQM ZQjH GdTaGs - (3JGL GdOjf YHO GdHGbi Gdjefis; (3GdbGVj YjGV , YjGV Hf ehSi Hf YjGV Hf YeQhf GdjMUHj GdSHJj, CHh GdaVd,J (B544 (3g` s ((3CMeO Hf eMeO Hf CMeO Hf eMeO Hf YHO GdQMef Hf YHO GdefYe GdTGaYi s)
(3ChdgG (B:s
(3GdMeO ddg Ydi cd MGd ef GdCMhGd aEfi CeYfJ GdfXQ aj eUfa GdTjN GdGeGe CHj GdaVd YjGV GdehShe HJYQja Mbhb GdeUWai s
(3BNQgG (B:s
(3BNQ GdehLhO efg bhdg GdbSe GdKGfi hajg CQHYI CHhGH GdHGH GdChd hajg NeSI aUhd GdaUd GdChd djS ajg eG jTcd s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B99 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B16s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3MGdI GdfSNI eJhSWI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3eJaQbGJs